Coerência quântica de estados de fenda: preparação e caracterização parcial de estados bipartidos assimétricos - Paula D'Avila Machado (2020)
The development of methods for preparing and characterizing quantum and entangled states is of great importance for the progress of quantum information and the development of new technologies. In this thesis, we study a slit state preparation of dimension D1 × D2 and presented experimental results for dimension 2 × 3. As for the characterization, we analyze how the quantum coherence of the parts of any bipartite state, provides us with information about the entanglement and the density matrix of the joint state. Also, we discuss how to obtain experimental quantum coherence of slit states, and present results obtained for qutrits.